Near‐infrared chemiluminescent carbon nanogels for oncology imaging and therapy. Issue 2 (17th March 2022) - Shen, Chenglong; Jiang, Tianci; Lou, Qing; Zhao, Wenbo; Lv, Chaofan; Zheng, Guangsong; Liu, Hangrui; Li, Pengfei; Dai, Lingling; Liu, Kaikai; Zang, Jinhao; Wang, Feng; et al.
Abstract: Carbon nanogels (CNGs) with dual ability of reactive oxygen species (ROS) imaging and photodynamic therapy have been designed with self‐assembled chemiluminescent carbonized polymer dots (CPDs). With efficient deep‐red/near‐infrared chemiluminescence (CL) emission and distinctive photodynamic capacity, the H2 O2 ‐driven chemiluminescent CNGs are further designed by assembling the polymeric conjugate and CL donors, enabling an in vitro and in vivo ROS bioimaging capability in animal inflammation models and a high‐performance therapy for xenograft tumors. Mechanistically, ROS generated in inflammatory sites or tumor microenvironment can trigger the chemically initiated electron exchange luminescence in the chemical reaction of peroxalate and H2 O2, enabling in vivo CL imaging. Meanwhile, part of the excited‐state electrons will transfer to the ambient H2 O or dissolved oxygen and in turn lead to the type I and type II photochemical ROS production of hydroxyl radicals or singlet oxygen, endowing the apoptosis of tumor cells and thus enabling cancer therapy. These results open up a new avenue for the design of multifunctional nanomaterials for bioimaging and antienoplastic agents. Abstract : Near‐infrared carbonized polymer dots with high quantum yield and self‐assembly property are rationally developed as monomers and self‐assemble into water‐soluble H2 O2 ‐driven chemiluminescent carbon nanogels, enabling an excellent in vitro and in vivo reactive oxygen species bioimaging capability in animal inflammation models and a high‐performance chemiluminescence‐guiding photodynamic therapy for solid tumors without autofluorescence interference.